Innovation platforms for agricultural development: Evaluating the mature innovation platforms landscape - Dror, Iddo; Cadilhon, Joseph J.; Schut, Marc; Misiko, Michael T.; Maheshwari, S. (Routledge, 2016)
Innovation Platforms (IPs) form the core of many Agricultural Research for Development programmes, stimulating multi-stakeholder collaboration and action towards the realization of agricultural development outcomes. This book enhances the body of knowledge of IPs by focusing on mature innovation platforms in agricultural systems research, including the crop and livestock sectors, and innovations in farmer co-operatives and agricultural extension services.